Finance for Small-Scale Commodity Processing: From Micro to Meso Finance - Summary of presentations and discussions - Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2005)
The main focus of the Workshop was on sustainable financial services for the first stages of commodity processing to support small-scale producers to move up the value-added chain and increase their efficiency and earnings in commodity production. In this regard, the Workshop carried out an assessment of investment opportunities and financing needs at the producer level. It further considered whether there is a lack of financial services in the middle-range or meso-credit category around USD 3,000 and above for rural commodity processing. The Workshop addressed the following topics: - Micro and meso-credit requirements of commodity producers and processors - Mechanisms currently employed by financial institutions, non-bank financial institutions, regional agricultural credit associations and donors in micro and meso-credit to the commodity sector and their experience in this area - Measures and options that would alleviate identified problems - The role of the Common Fund for Commodities and other financial and development institutions in this sector.
Keywords: 330